Quantifying the Value of Introducing an Oral Drug Delivery Option for Edaravone: A Review of Analyses Evaluating the Economic Impact of Oral versus Intravenous Formulations - Ronquest NA; Paret K; Lucas A; Ciepielewska M; Hagan M (Dove Medical Press, 2022)
Naoko A Ronquest,1 Kyle Paret,1 Aaron Lucas,1 Malgorzata Ciepielewska,2 Melissa Hagan2 1Health Economics, RTI Health Solutions, Research Triangle Park, Durham, NC, USA; 2Medical Affairs-HEOR/RWE/Publications, Mitsubishi Tanabe Pharma America, Inc, Jersey City, NJ, USACorrespondence: Naoko A Ronquest, Health Economics, RTI Health Solutions, 3040 East Cornwallis Road, Research Triangle Park, Durham, NC, 27709, USA, Tel +1 919 597 5122, Fax +1 919 541 7222, Email nronquest@rti.orgBackground: Drug formulation and route of administration can have an impact on not only patients' quality of life and disease outcomes but also costs of care. It is essential for decision makers to use appropriate economic modeling methods to guide drug coverage policies and to support patients' decision-making.Purpose: To illustrate key cost considerations for decision makers in economic evaluation of innovative oral formulations as alternatives to intravenous medication.Materials and Methods: A structured literature review was conducted using the PubMed database to examine methods used for quantifying the economic impact of introducing a new oral pharmaceutical formulation as an alternative to intravenous medication. To illustrate the methods described in this review, a cost-minimization analysis was conducted to quantify the impact of introducing an oral formulation of a medication originally developed as an intravenous treatment for amyotrophic lateral sclerosis.Results: We identified 14 published evaluations of oral and intravenous formulations from 10 countries across a variety of disease areas. The identified studies used cost-effectiveness (n=10), cost-minimization (n=2), and cost-calculation (n=2) modeling approaches. All but one (13/14) reported outcomes from payers' perspective, while societal perspectives were also incorporated in 3 of the reviewed evaluations. One study estimated costs from a public hospital's perspective. Only a subset of the identified studies accounted for the effects of safety (n=6) or efficacy (n=8) differences on treatment costs when estimating the costs of a formulation choice. Many studies that omitted these aspects did not include rationales for their decisions.Conclusion: We found significant design variations in published models that estimated the impact of an additional formulation option on the treatment costs to payers and the society. Models need to be accompanied with clear descriptions on rationales for their time horizons and assumptions on how different formulations may affect healthcare costs from the selected perspectives.Keywords: cost-effectiveness analysis, cost-minimization, decision makers, formulation comparison, amyotrophic lateral sclerosis